Peningkatan Aktivitas Belajar IPS melalui Strategi Pembelajaran Aktif Tipe Team Quiz - Felix Welu; Berty Sadipun; Frumensius Dole (Journal of Elementary School (JOES), 2018)
The study was to know the improvement of students learning activities by using active learning method by the application of Team Quiz. The study was a classroom action research. The subject was 22 students from grade IV SDI Bhoanawa 1. The data collection was conducted through observation, field note and interview. The result showed the improvement of students learning activities. It was proved by the percentage score of the activities in cycle I for 62% with category 'quite active' and 76 % in cycle II with category 'active'. In conclusion, active teaching strategy with team quiz can improve social learning activities. Keywords: Teaching Activities, Active Teaching Strategy, Team Quiz